Optimizing oil and xanthorrhizol extraction from Curcuma xanthorrhiza Roxb. rhizome by supercritical carbon dioxide - Salea, Rinaldi (Springer India, 2014)
Oil and xanthorrhizol extraction from Curcuma xanthorrhiza Roxb. rhizome by supercritical carbon dioxide was optimized using Taguchi method. The factors considered were pressure, temperature, carbon dioxide flowrate and time at levels ranging between 10–25 MPa, 35–60 °C, 10–25 g/min and 60–240 min respectively. The highest oil yield (8.0 %) was achieved at factor combination of 15 MPa, 50 °C, 20 g/min and 180 min whereas the highest xanthorrhizol content (128.3 mg/g oil) in Curcuma xanthorrhiza oil was achieved at a factor combination of 25 MPa, 50 °C, 15 g/min and 60 min. Soxhlet extraction with n-hexane and percolation with ethanol gave oil yield of 5.88 %, 11.73 % and xanthorrhizol content of 42.6 mg/g oil, 75.5 mg/g oil, respectively. The experimental oil yield and xanthorrhizol content at optimum conditions agreed favourably with values predicted by computational process. The xanthorrizol content extracted using supercritical carbon dioxide was higher than extracted using Soxhlet extraction and percolation process.